Surgery for the acute abdomen in adults with leukaemia. Issue 732 (October 1986) - Martell, R. W.; Jacobs, P.
Abstract : In a retrospective analysis five of 104 patients with acute leukaemia undergoing cytotoxic chemotherapy developed abdominal signs requiring emergency surgical exploration. Two common features in these patients were the inclusion of cytosine arabinoside in their treatment regimen and a necrotizing lesion involving the terminal ileum, appendix, and right colon. Appendicectomy was performed in two and hemicolectomy in three. Of the patients receiving high-dose cytosine arabinoside one died in the immediate post-operative period and two after recovery from surgery but before marrow regeneration; the remaining two patients received conventional dose cytosine arabinoside, and both recovered. The inclusion of this agent is standard in modern treatment programmes, resulting in significant improvement in long-term disease-free survival, so that a greater awareness of this complication is necessary. Early surgery, utilizing modern support techniques, is recommended as feasible and appears to offer the only realistic chance of survival.